KAJIAN PERJANJIAN PENETAPAN HARGA LAYANAN PESAN SINGKAT (SHORT MESSAGE SERVICE) ANTARA PT XL TBK DAN PT TELKOMSEL DENGAN OPERATOR SELULER TERKAIT PERSAINGAN USAHA TIDAK SEHAT (STUDI KASUS PERJANJIAN PENETAPAN HARGA SMS OFF-NET) - Wedha Arisanthi, Ida Ayu; Sukihana, Ida Ayu; Sri Indrawati, Anak Agung (Kertha Wicara : Journal Ilmu Hukum; Vol. 02, No. 02, April 2013)
This paper entitled “Study Contract of Pricing Short Message Service Determination Between PT.XL TBK and PT.Telkomsel against the cellular operators related with unfair business competition”. This paper uses normative analysis method. The formed of Telecommunications of Law 1999 No.36 trigger a competition in telecommunication. Now as a result of the law about unfair competition had been regulated in The Prohibition of Monopolistic Practices and Unfair Business Competition 1999 No.5
Keywords: Contract, Short Messages Service, Cellular Operator, Unfair Competition.